Dentition, nutritional status and adequacy of dietary intake in treatment naïve head and neck cancer patients. Issue 3 (March 2020) - Kubrak, Catherine; Farhangfar, Arazam; Woynorowski, Matthew; Jha, Naresh; Preshing, William; Baracos, Vickie
Abstract: Objectives: To examine the relationship of reduced numbers of occluding teeth and dietary intake (DI), nutrition impact symptoms (NIS), and weight loss (WL) in head and neck cancer (HNC) patients. Methods: As a part of the standard of care, treatment-naïve HNC patients (n = 104) completed dental evaluation (number of teeth, total anterior/posterior occlusal teeth, Eichner Index (EI) classification), WL, DI questionnaire and HNC Symptom Checklist©. Descriptive statistics (Kruskal-Wallis, Fisher-exact, χ 2 tests) and (uni-) multi-variable logistic regression. Results: Overall, 42, 45 and 13% of patients were in EI-class A, B and C with a median of 8, 3, and 0 total posterior occlusal teeth. EI-class B/C patients were older, more likely to have impaired DI (OR = 3.88; 95%CI:1.63–9.26; P = 0.002) and reported interference with DI by 11 NIS (p < 0.05). DI was, however, reported as unimpaired in 77, 49 and 39% of patients in EI-class A, B and C, respectively. The subset of EI-class B/C patients with impaired DI, had more NIS interference with DI ( P < 0.05; difficulty chewing, pain, early satiety, lack of energy); EI-class C patients additionally had dry mouth, thick saliva and dysphagia ( P < 0.05). In logistic regression, EI-classes B/C patients with reduced (vs unimpaired) DI were more likely to have ≥5% WL (OR = 10.1; 95%CI:2.0–50.0), higher NIS interference (range OR 4.3–10.7). Conclusions: More than half of these HNC patients had reduced numbers of occlusal teeth or were edentulous. EI-class B/C patients did not necessarily have impaired DI, however the combination of EI-class B/C and a constellation of NIS, associated with reduced DI. Clinical significance: Treatment naïve head and neck cancer (HNC) patients with reduced occlusal and masticatory performance (Eichner Index B/C) and reduced dietary intake are at high risk for weight loss. Identifying HNC patients at risk may improve their oral health, dietary intake and reduce their risk of weight loss. Abstract : Diet; Oral medicine; Oncology; Nutrition; Head and neck cancer; Dietary intake; Eichner index; Weight loss; Nutrition impact symptoms; Dentition; Teeth; Occlusal support